INFLUENCE OF SODIUM SUCCINATE SINGLE APPLICATION ON PROCESSES OF THE FOOTBALLERS’ RECOVERYAFTER PHYSICAL ACTIVITIES IN DIFFERENT INTENSITY ZONES - Чернєв О. В. (World of Medicine and Biology, 2015)
In the training process should be paid attention to the work, both in aerobic and anaerobic energy systems. If the work cycle prevails in the aerobic zone (modes 1-3) this has a negative effect on anaerobic capacity. Conversely work in the anaerobic zone (4a, 4b) directed at the development of high-speed qualities leads to a deterioration of the general stamina. It is clear that a good athletic performance is possible only due to the optimal ratio of different physical qualities. The aim of the study was to determine what changes occurred in a single application of sodium succinate that influenced on the footballers’ recovery processes after physical activities in different intensity zones. Methods and organization of the research. In order to determine the influence of sodium succinate single application on the footballers’ recovery processes after physical activities in different intensity zones were surveyed 84sportsmen. The examination was conducted in the period of educational and training meetings (ETM) in January, February and July 2012-2013. Results of the research and discussion. It was studied the influence of sodium succinate single application on the footballers at a dose of 5 mg per 1 kg body weight for 1 hour prior the training sessions in different intensity zones on the dynamics of lactate content in the blood and heart rate fluctuations, the totality of which reflects the efficiency of the recovery processes after physical activities. Application of sodium succinate had a positive impact on the dynamics of lactate content both the players in the peripheral blood the number of deformed erythrocytes was not rising above the limits recommended by the reference values and among athletes whose number of deformed erythrocytes increased substantially. Analysis of changes in heart rate indicators indicated that the groups of players taking sodium succinate, recovery process is more pronounced than among the sportsmen who did not take the medicine. Thus, it was found that the use of sodium succinate has a positive impact on the footballers’ recovery processes after intensive physical activities under aerobic and anaerobic orientation of the training process in different intensity zones. Conclusions. A single application of sodium succinate increases the speed and efficiency of the footballers’ recovery processes after training sessions, which showed their dynamics of lactate content in the blood after exercise in the aerobic zone of intensity ( Zone 3 ) for 3 min. - 6,47 ± 0,41 mmol.l - 1 vs the control group mmol.l 8,69 ± 0,49 - 1 (p ≤ 0,05), respectively, for 7 min. - 5,43 ± 0,51 mmol.l - 1 vs. 6,02 ± 0,48 mmol.l -1 and 15 min. - 4,11 ± 0,42 mmol.l - 1 vs 5,47 ± 0,37 mmol.l - 1 (p ≤ 0,05); after exercise in the anaerobic zone of intensity (4a, 4b zones ) for 3 min. - 18,71 ± 0,76 mmol.l - 1 against rates of the control group 23,69 ± 0,89 mmol.l - 1 (p ≤ 0,05), respectively, for 7 min. - 9,34 ± 0,51 mmol.l - 1 vsmmol.l 11,42 ± 0,48 - 1 (p ≤ 0,05) and 15 min. - 6,72 ± 0,28 mmol.l - 1 vs 7,47 ± 0,36 mmol.l - 1 (p ≤ 0,05). It was found in the work that the speed and efficiency of the recovery processes after training sessions of the sportsmen taking sodium succinate increased, which showed their dynamics of lactate content in the blood after exercise in the aerobic zone of intensity, as well as positive changes in heart rate deceleration.